2019
DOI: 10.7224/1537-2073.2017-041
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis, Anxiety, and Depression in the United Arab Emirates

Abstract: Background: Depression rates in the multiple sclerosis (MS) population in the Arab world have rarely been reported despite people with MS generally having higher rates of depression. We examined depression rates in 416 people with MS versus the general population of Abu Dhabi, United Arab Emirates, and their treatment. Methods: A retrospective medical record review of 416 people with MS (age range, 16–80 years) followed up at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Most of the studies were cohort studies without control subjects and overall, global prevalence rates for depression and anxiety ranged from 21.1–59.4% to 28.1–57.0% for depression and anxiety, respectively. Several studies reported depression at ~ 35% [ 40 49 ] and anxiety at ~ 55% in PwMS [ 43 46 , 49 52 ], and exceptionally low rates were observed for studies performed in Abu Dhabi (10.8–17.5% for depression and 4.8–20.0% for anxiety) [ 53 , 54 ]. Jun-O'Connell et al reported an increased prevalence of bipolar disorder in PwMS in a cohort from the US (type 1 was more significantly more prevalent than type 2 in the study group: 60% versus 30%, respectively), although this study lacked a control group.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies were cohort studies without control subjects and overall, global prevalence rates for depression and anxiety ranged from 21.1–59.4% to 28.1–57.0% for depression and anxiety, respectively. Several studies reported depression at ~ 35% [ 40 49 ] and anxiety at ~ 55% in PwMS [ 43 46 , 49 52 ], and exceptionally low rates were observed for studies performed in Abu Dhabi (10.8–17.5% for depression and 4.8–20.0% for anxiety) [ 53 , 54 ]. Jun-O'Connell et al reported an increased prevalence of bipolar disorder in PwMS in a cohort from the US (type 1 was more significantly more prevalent than type 2 in the study group: 60% versus 30%, respectively), although this study lacked a control group.…”
Section: Resultsmentioning
confidence: 99%
“…After excluding duplicate papers and irrelevant articles, 534 potentially eligible studies remained. Finally, 32 articles ( Noy et al, 1995 ; Nicholl et al, 2001 ; Korostil and Feinstein, 2007 ; Uguz et al, 2008 ; Poder et al, 2009 ; Gay et al, 2010 , 2017 ; Suh et al, 2010 ; Garfield and Lincoln, 2012 ; Jones et al, 2012 ; van der Hiele et al, 2012 ; Leonavicius and Adomaitiene, 2013 ; Askari et al, 2014 ; Terrill et al, 2015 ; Marck et al, 2016 ; Marrie et al, 2018 ; Orr et al, 2018 ; Panda et al, 2018 ; Pham et al, 2018 ; Gascoyne et al, 2019 ; Gill et al, 2019 ; Henry et al, 2019 ; Kotan et al, 2019 ; Schiess et al, 2019 ; Chertcoff et al, 2020 ; Hanna and Strober, 2020 ; Karimi et al, 2020 ; Podda et al, 2020 ; Reyes et al, 2020 ; Wallis et al, 2020 ; Zanghì et al, 2020 ; Ramezani et al, 2021 ) with 15,853 participants were found to be eligible in the analyses, as shown in Table 1 . The flow diagram of the search and study selection process was shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%